Effect of hexavalent chromium on proliferation and differentiation to adipocytes of 3T3-L1 fibroblasts - Martini, Claudia Noemí (2014)
Heavy metals contamination has become an important risk factor for public health and the environment. Chromium is a frequent industrial contaminant and is also used in orthopaedic joint replacements made from cobalt–chromium-alloy. Since hexavalent chromium (Cr(VI)) was reported as genotoxic and carcinogenic in different mammals, to further evaluate its cytotoxicity, we investigated the effect of this heavy metal in the proliferation and differentiation to adipocytes of 3T3-L1 fibroblasts. These cells, after the addition of a mixture containing insulin, dexamethasone and methylisobutylxanthine, first proliferate, a process known as mitotic clonal expansion (MCE), and then differentiate to adipocytes. In this differentiation process a key transcription factor is induced: peroxisome proliferator-activated receptor gamma (PPAR gamma). We found that treatment of 3T3-L1 fibroblasts with potassium chromate inhibited proliferation in exponentially growing cells and MCE as well as differentiation. A decrease in PPAR gamma content, evaluated by western blot and immunofluorescence, was found in cells differentiated in the presence of chromium. On the other hand, after inhibition of differentiation with chromium, when the metal was removed, differentiation was recovered, which indicates that this may be a reversible effect. We also found an increase in the number of micronucleated cells after treatment with Cr(VI) which is associated with genotoxic effects. According to our results, Cr(VI) is able to inhibit proliferation and differentiation to adipocytes of 3T3-L1 fibroblasts and to increase micronucleated cells, which are all indicative of alterations in cellular physiology and therefore, contributes to further elucidate the cytotoxic effects of this heavy metal.